Exploring Regularities and Dynamic Systems in L2 Development. Issue 1 (March 2015) - Lenzing, Anke; Hulstijn, Jan H.; Ellis, Rod; Eskildsen, Søren W.
<x xml:space="preserve">Abstract</x> This article focuses on a theoretical and empirical exploration of developmental trajectories and individual learner variation in second language (L2) acquisition. Taking a processability perspective, I view learner language as a dynamic system that includes predictable universal developmental trajectories as well as individual learner variation, where the latter is not precisely predictable. Both dimensions are subject to specific processing constraints that are determined by the architecture of the human language processor. I claim that this view of L2 acquisition is compatible with the core notions of Dynamic Systems Theory. I present results from an empirical study of beginning L2 learners of English with German as their first language to support this claim. The results show (1) that there are developmental regularities in L2 acquisition that are common to all learners and (2) that the learner variation that occurs is consistent with the constraints of the developing L2 system.